Positive electrode material, positive electrode, and secondary battery

By using single-particle positive electrode active materials of different particle sizes in the positive electrode material of the secondary battery and applying a boron-cobalt coating, the irreversible capacity and cycle performance deterioration of the secondary battery when using the negative electrode of the silicon-type active material is solved, and the problem of deterioration of the irreversible capacity and circulation performance of the secondary battery is achieved. High density electrodes and improved service life.

CN119452479APending Publication Date: 2025-02-14LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380049517.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2023-09-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When using the negative electrode of the silicon-based active material in the existing secondary batteries, there are problems of deterioration of irreversible capacity and cycling performance, and the selection or combination of the positive electrode materials has a great impact on the battery performance.

Method used

A positive electrode material comprising the first positive electrode active material and the second positive electrode active material, both of which are in the form of a single particle, and a coating containing boron and cobalt is applied to its surface to improve interface resistance and electrode density.

Benefits of technology

By using single-particle positive electrode active materials of different particle sizes and applying boron-cobalt coating, high-density electrode and low-efficiency characteristics are achieved, reducing the resistance difference with the negative electrode, and significantly improving the room temperature service life and high-temperature service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206142750000211
    Figure BDA0005206142750000211
  • Figure BDA0005206142750000221
    Figure BDA0005206142750000221
  • Figure BDA0005206142750000231
    Figure BDA0005206142750000231
Patent Text Reader

Abstract

The present invention relates to a positive electrode material, and a positive electrode and a secondary battery comprising the same, the positive electrode material comprising: a first positive electrode active material in the form of a single particle and having a coating layer comprising boron (B) and cobalt (Co) provided on at least a part of a surface thereof; and a second positive electrode active material having a particle diameter larger than that of the first positive electrode active material, in the form of a single particle, and having a coating layer containing boron (B) and cobalt (Co) provided on at least a portion of a surface thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode material, a positive electrode, and a secondary battery. This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0125334 filed on September 30, 2022 in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. Background Art

[0002] Secondary batteries are commonly used not only in portable devices but also in electric vehicles (EVs) and hybrid electric vehicles (HEVs) driven by an electric drive source.

[0003] Since such secondary batteries not only have the major advantage of being able to significantly reduce the use of fossil fuels but also have the advantage of not generating any byproducts caused by the use of energy, secondary batteries have attracted attention as a new energy source that is environmentally friendly and improves energy efficiency.

[0004] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, etc. In addition, electrodes such as the positive electrode and the negative electrode may have an electrode active material layer disposed on a current collector.

[0005] As the utilization rate of secondary batteries increases, a variety of battery performances are required. For example, attempts have been made to apply silicon-based active materials to negative electrodes to develop high-capacity batteries, but silicon-based active materials have the problem of high initial irreversibility. Although attempts have been made to adjust the composition of the positive or negative electrode or to add additives to improve battery performance, the selection or combination of wrong materials may have an adverse effect on the performance of the final battery. Therefore, it is necessary to study the selection or combination of materials for the positive or negative electrode to improve battery performance. Summary of the invention

[0006] [Technical issues]

[0007] The present invention is directed to providing a positive electrode material, a positive electrode containing the same, and a secondary battery, wherein the positive electrode material, when used together with a negative electrode using a silicon-based active material, can provide the irreversible capacity of the negative electrode, can prevent the cycle performance degradation problem by reducing the resistance difference with the negative electrode, and can realize a high-density electrode.

[0008] [Technical solution]

[0009] One aspect of the present invention provides a positive electrode material comprising: a first positive electrode active material, which is in the form of a single particle and has a coating containing boron (B) and cobalt (Co) disposed on at least a portion of its surface; and a second positive electrode active material, which has a particle size larger than the particle size of the first positive electrode active material, is in the form of a single particle and has a coating containing boron (B) and cobalt (Co) disposed on at least a portion of its surface.

[0010] Another aspect of the present invention provides a positive electrode for a secondary battery, comprising: a current collector; and a positive electrode active material layer disposed on the current collector and comprising the positive electrode material of the above aspect.

[0011] Another aspect of the present invention provides a secondary battery comprising the positive electrode, the negative electrode and the separator according to the above aspect.

[0012] According to yet another aspect of the present invention, the negative electrode includes a silicon-based active material.

[0013] [Beneficial Effects]

[0014] According to the aspects described in this specification, by using both the first positive electrode active material and the second positive electrode active material having different particle sizes and in the form of single particles as the positive electrode active material, a high-density electrode can be achieved and has low efficiency characteristics, so when the positive electrode active material is used with a negative electrode using a silicon-based active material, the irreversible capacity of the negative electrode can be provided. In addition, by applying a boron coating on both the first positive electrode active material and the second positive electrode active material having different particle sizes to increase the interface resistance of the positive electrode, thereby improving the rapid reduction of the discharge end resistance, the available voltage of the silicon-based active material of the negative electrode can be reduced to significantly improve the room temperature service life. In addition, when a cobalt coating is formed on the first positive electrode material and the second positive electrode material before forming the boron coating, cobalt and boron are simultaneously present in the coating, so the positive electrode resistance can be improved by cobalt, and the rapid resistance reduction of the discharge end resistance can be improved by boron. DETAILED DESCRIPTION

[0015] Hereinafter, the present invention will be described in more detail to help understand the present invention. The present invention can be implemented in various forms and is not limited to the aspects described herein. In this case, the terms or words used in the specification and claims should not be interpreted as limited to the typical or dictionary meanings, and should be interpreted with the meaning and concept consistent with the technical concept of the present invention based on the principle that the inventor can appropriately define the concept of the term in order to describe his / her own invention in the best way.

[0016] In the present invention, the terms "include", "comprising" or "having" are intended to indicate the existence of implemented features, numbers, steps, constituent elements or any combination thereof, and should be understood as meaning not excluding the existence or additional possibility of one or more other features or numbers, steps, constituent elements or any combination thereof.

[0017] The case where a part such as a layer exists “above” or “on” another part includes not only the case where the part exists “directly” “above” another part, but also the case where another part exists therebetween. Conversely, the case where a part exists “directly” “above” another part means that no other part exists therebetween. In addition, the case where it is located “above” or “on” a reference part means being located above or below the reference part, and does not necessarily mean being located “above” or “on” in the opposite direction of gravity.

[0018] In this specification, the particle size refers to the average particle size represented by D50. D50 refers to the particle size of 50% of the volume cumulative particle size distribution based on the positive electrode active material powder. The average particle size D50 can be measured using a laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, and the resulting dispersion is then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) to irradiate the dispersion with an ultrasonic wave of about 28kHz at an output of 60W, and then obtain a volume cumulative particle size distribution diagram, and then the average particle size can be measured by obtaining a particle size corresponding to 50% of the volume cumulative amount.

[0019] In this specification, "primary particles" refer to particles that do not have grain boundaries in appearance when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope. "Average particle size of primary particles" refers to the arithmetic mean of particle sizes calculated after measuring the particle sizes of primary particles observed in a scanning electron microscope image.

[0020] In this specification, "secondary particles" are particles formed by aggregation of a plurality of primary particles.

[0021] In this specification, "single particle" is a term used to distinguish single particles from positive electrode active material particles in the form of secondary particles formed by the aggregation of tens to hundreds of primary particles commonly used in the prior art, and is a concept that includes single particles composed of one primary particle and aggregated particles of 10 or less primary particles.

[0022] In the present specification, the "particle" may include any or all of a single particle, a secondary particle, and a primary particle.

[0023] In this specification, the "specific surface area" is measured by the BET method, and can be specifically calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mino II manufactured by BEL Japan.

[0024] In this specification, the content of each component of the positive electrode active material can be measured by inductively coupled plasma mass spectrometry (ICP). Specifically, the sample to be tested is pretreated with acid and then measured using an ICP-OES (Perkin Elmer, Optima 7300DV) device.

[0025] The positive electrode material of one aspect of the present specification is characterized in that it comprises: a first positive electrode active material in the form of a single particle and having a coating containing boron (B) and cobalt (Co) disposed on at least a portion of its surface; and a second positive electrode active material having an average particle size (D50) greater than the average particle size (D50) of the first positive electrode active material, in the form of a single particle and having a coating containing boron (B) and cobalt (Co) disposed on at least a portion of its surface. According to the present invention, by using two single particles with different average particle sizes (D50) as positive electrode active materials, the gaps between the positive electrode active material particles with a large particle size are filled with positive electrode active material particles with a small particle size to enhance the electrode density, and the contact area between the positive electrode active material particles is increased, so that the effect of improving the energy density can be obtained. In addition, the single particle form can have low efficiency characteristics, so that when used with a negative electrode using a silicon-based active material, the irreversible capacity of the negative electrode can be provided. In addition, by applying a coating containing boron and cobalt on both the first positive electrode active material and the second positive electrode active material to increase the interface resistance of the positive electrode, the rapid reduction of the discharge end resistance can be improved.

[0026] According to one aspect, the discharge end resistance of a battery containing the above-mentioned positive electrode material can be in a range of 2.6Ω or more, for example, 2.65Ω or more, and in a range of 4Ω or less, for example, 3.5Ω or less. Preferably, the room temperature service life measured by the method described in the embodiment is 90% or more, for example, 91% or more, 92% or more, 93% or more, 94% or more, 95% or more, 97% or more, or 98% or more. Preferably, the high temperature service life measured by the method described in the embodiment is 87% or more, for example, 88% or more, 90% or more, 92% or more, 93% or more, 94% or more, 95% or more, or 97% or more.

[0027] According to one aspect, the D50 of the first positive electrode active material may be 1 μm or more and 7 μm or less, and the D50 of the second positive electrode active material may be 3 μm or more and 12 μm or less. Specifically, the D50 of the first positive electrode active material may be 1 μm or more, 2 μm or more, or 3 μm or more and 7 μm or less, 6 μm or less, 5 μm or less, or 4 μm or less. The D50 of the second positive electrode active material may be 3 μm or more, 4 μm or more, or 5 μm or more and 12 μm or less, 11 μm or less, 10 μm or less, 9 μm or less, 8 μm or less, or 7 μm or less.

[0028] The average particle size of the second positive electrode active material may be 0.5 μm to 7 μm larger than the average particle size of the first positive electrode active material, for example, 0.8 μm to 5 μm or 1 μm to 4 μm. When the average particle size difference is less than 0.5 μm, the thickness of the coated electrode increases due to the decrease in the tap density (g / cc) of the positive electrode active material, which may cause the rolling characteristics during the electrode rolling to deteriorate, and when the particle size difference exceeds 7 μm, the imbalance between the two particles during the electrochemical reaction may increase due to the increase in the specific surface area difference.

[0029] According to one aspect, the weight ratio of the first positive electrode active material to the second positive electrode active material can be 1:9 to 9:1, such as 3:7 to 7:3, specifically 4:6 to 6:4, or 5:5. The closer the weight ratio of the first positive electrode active material to the second positive electrode active material, the better the electrode density.

[0030] According to one aspect, the first positive electrode active material and the second positive electrode active material may each include a lithium nickel-based oxide having a molar fraction of nickel of 50 mol % or more in the metal element other than lithium. The first positive electrode active material and the second positive electrode active material may have the same composition and may differ only in average particle size, or may differ in both composition and average particle size.

[0031] The lithium nickel-based oxide may be a lithium nickel cobalt manganese-based oxide in which the molar fraction of nickel in the metal element other than lithium is 50 to 99 mol %, for example, 60 to 99 mol %, specifically 80 to 98 mol %.

[0032] According to one aspect, the lithium nickel-based oxide may have a composition represented by the following [Chemical Formula 1].

[0033] [Chemical formula 1]

[0034] Li 1+x (Ni a Co b Mn c M d )O2

[0035] In Chemical Formula 1,

[0036] M is one or more selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and

[0037] x, a, b, c, and d are 0 ≤ x ≤ 0.2, 0.50 ≤ a < 1, 0 < b ≤ 0.25, 0 < c ≤ 0.25, 0 ≤ d ≤ 0.1, and a + b + c + d = 1, respectively.

[0038] In [Chemical Formula 1], M is one or more selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, preferably one or more selected from the group consisting of Al, Zr, Y, Mg, and Ti, and more preferably Al or Zr. The M element is not necessarily included, but when included in an appropriate amount, it can be used to promote particle growth during firing and improve the stability of the crystal structure.

[0039] a represents the molar ratio of nickel among the metals other than lithium in the lithium nickel-based oxide, and can be 0.5 ≤ a ≤ 0.99, 0.6 ≤ a ≤ 0.99, 0.7 ≤ a ≤ 0.98, or 0.8 ≤ a ≤ 0.98.

[0040] b represents the molar ratio of cobalt among the metals other than lithium in the lithium nickel-based oxide, and can be 0 < b ≤ 0.25, 0.01 ≤ b ≤ 0.2.

[0041] c represents the molar ratio of manganese among the metals other than lithium in the lithium nickel-based oxide, and can be 0 < c ≤ 0.25, 0.01 ≤ c ≤ 0.2.

[0042] d represents the molar ratio of the M element among the metals other than lithium in the lithium nickel-based oxide, and can be 0 ≤ d ≤ 0.1, or 0 ≤ d ≤ 0.08.

[0043] Preferably, the lithium nickel-based oxide can be a lithium nickel cobalt manganese oxide doped with Zr. During doping with Zr, the effect of suppressing particle cracking during electrode rolling is even better. In this case, based on the total weight of the positive electrode material, the content of Zr can be 3,000 ppm to 6,000 ppm, preferably 3,500 ppm to 5,500 ppm, and more preferably 4,000 ppm to 5,000 ppm. When the content of Zr satisfies the above range, the service life characteristics can be improved due to excellent structural stability.

[0044] According to one aspect, each coating of the first positive active material and the second positive active material includes a coating containing boron (B) and a coating containing cobalt (Co). The coating containing cobalt (Co) is disposed on at least a portion of the surface of the first positive active material or the second positive active material, or is disposed between the coating containing boron (B) and at least a portion of the surface of the first positive active material or the second positive active material.

[0045] The above-mentioned coating containing boron is formed on the surface of the lithium nickel-based oxide. In this case, the coating containing boron may cover the entire surface of the lithium nickel-based oxide, but is not limited thereto, and may cover only a portion of the lithium nickel-based oxide. The coating containing boron may be arranged continuously with each other on the surface of the lithium nickel-based oxide, but two or more portions thereof may be arranged at intervals, and at least a portion thereof may be arranged in the form of an island.

[0046] When a coating containing boron (B) is formed on the surface of the lithium nickel-based oxide, the rapid reduction of the resistance at the end of the discharge can be improved by increasing the interface resistance of the positive electrode. Therefore, the resistance difference with the negative electrode can be reduced, so that the available voltage of the silicon-based active material of the negative electrode can be reduced, so that the cycle performance of the battery can be prevented from deteriorating and the room temperature service life can be improved. In addition, the contact between the electrolyte and the lithium nickel-based oxide is minimized by the coating containing boron, thereby suppressing the occurrence of side reactions between the electrolyte and the lithium nickel-based oxide and the dissolution of transition metals, so that the effect of improving the service life characteristics can be obtained, and the particle cracking during rolling is also reduced.

[0047] In this case, the content of boron (B) may be 200 ppm to 3,000 ppm, for example, 300 ppm to 2,000 ppm, 300 ppm to 1,800 ppm, 400 ppm to 1,500 ppm, or 500 ppm to 1,500 ppm, based on the weight of each of the first positive electrode active material and the second positive electrode active material. When the content of boron (B) is less than 200 ppm based on the weight of each of the first positive electrode active material and the second positive electrode active material, a coating cannot be sufficiently formed on the surface of the positive electrode active material, thereby failing to increase the interface resistance of the positive electrode, and when the content of boron (B) exceeds 3,000 ppm, the surface of the positive electrode active material may be completely covered by the coating, thereby preventing the electrochemical reaction from occurring properly.

[0048] According to one aspect, the boron content in the first positive electrode active material may be higher than the boron content in the second positive electrode active material. Since the first positive electrode active material having a relatively small particle size has a larger specific surface area than the second positive electrode active material, the side reaction with the electrolyte can be effectively controlled so that the boron content is higher than the boron content of the second positive electrode active material. By suppressing the side reaction with the electrolyte as described above, the resistance characteristics and high temperature service life can be improved.

[0049] According to one aspect, the weight ratio (A / B) of the boron content A in the first positive electrode active material to the boron content B in the second positive electrode active material may be 1 to 3, for example, 1.5 to 3, or 1 to 2.5, specifically 1.5 to 2.5 or 1.5 to 2. For example, the boron (B) content in the first positive electrode active material may be 600 ppm to 3,000 ppm, for example, 700 ppm to 1,500 ppm, based on the weight of the first positive electrode active material, and the boron (B) content in the second positive electrode active material may be 200 ppm to 1,000 ppm, for example, 300 ppm to 700 ppm, or 400 ppm to 650 ppm, based on the weight of the second positive electrode active material.

[0050] According to additional aspects, the first positive active material and the second positive active material may further include a coating containing cobalt (Co), which is disposed on at least a portion of the surface or between a coating containing boron (B) and at least a portion of the surface of a single particle. In this case, the coating containing cobalt may cover the entire surface of the lithium nickel-based oxide, but is not limited thereto, and may only cover a portion of the lithium nickel-based oxide. The coating containing cobalt may be arranged continuously with each other on the surface of the lithium nickel-based oxide, but two or more portions thereof may be arranged at intervals, and at least a portion thereof may be arranged in the form of an island. When a coating containing cobalt is applied, a coating containing boron may also be disposed on the coating containing cobalt, and may also be disposed in direct contact with the surface of the lithium nickel-based oxide where there is no coating containing cobalt. In one example, there is no intermediate layer between the boron coating and the lithium nickel-based oxide except for the cobalt coating. The positive electrode resistance can be improved by applying a coating containing cobalt. However, when a coating containing cobalt is applied, the discharge end resistance is significantly improved, thereby increasing the available voltage of the silicon-based active material contained in the negative electrode, which may lead to deterioration of the cycle characteristics, but in the aspects described in this specification, the presence of a coating containing boron can increase the interfacial resistance of the positive electrode, thereby slowing down the rapid decrease in the discharge end resistance.

[0051] Based on the weight of each of the first positive electrode active material and the second positive electrode active material, the content of cobalt contained in the coating layer containing cobalt (Co) may be 5,000 ppm to 50,000 ppm, for example, 5,000 ppm to 30,000 ppm, 10,000 ppm to 30,000 ppm, 15,000 ppm to 25,000 ppm, or 17,000 ppm to 23,000 ppm. When the cobalt (Co) content satisfies the above range, it is beneficial to improve the positive electrode resistance.

[0052] In some embodiments, in each of the first positive active material and the second positive active material, the ratio of the amount of boron to the amount of cobalt in the coating is 0.001 to 1, preferably 0.02 to 0.8, 0.02 to 0.7, 0.03 to 0.6, 0.04 to 0.5, 0.05 to 0.4, or 0.06 to 0.3, more preferably 0.005 to 0.175, 0.02 to 0.15, or 0.025 to 0.1. The ratio is calculated as ppm content. When the ratio is less than 0.001, the effect of the presence of boron in the coating may be minimal. When the ratio exceeds 0.2, boron may be excessively included compared to cobalt, which may have a negative impact on battery performance.

[0053] In some embodiments, a ratio of the cobalt content to the boron content (Co / B) contained in the entire first positive electrode active material and the second positive electrode active material may be 5 to 70, for example, 7 to 60, 20 to 55, or 25 to 50. Here, the cobalt includes cobalt contained in a single particle in addition to the cobalt in the coating layer.

[0054] According to one aspect, the BET specific surface area of ​​the first positive electrode active material and the second positive electrode active material or the positive electrode material may be 0.2 to 1 m 2 / g, preferably 0.25 to 0.85m 2 When the specific surface area of ​​the lithium nickel-based oxide is large, side reactions with the electrolyte may occur frequently, resulting in deterioration of the service life characteristics, and when the specific surface area of ​​the positive electrode active material is reduced, the side reactions with the electrolyte are reduced, thereby obtaining an effect of improving the service life characteristics.

[0055] One aspect provides a method for preparing a positive electrode active material, and the method comprises:

[0056] preparing a single particle positive electrode active material by mixing a transition metal precursor and a lithium raw material and then firing the resulting mixture;

[0057] washing the positive electrode active material with water; and

[0058] A coating layer including boron (B) and cobalt (Co) is formed on at least a portion of a surface of the positive electrode active material.

[0059] According to one aspect, forming a coating layer including boron (B) and cobalt (Co) on at least a portion of a surface of a positive electrode active material may include: forming a coating layer including cobalt (Co) before forming a coating layer including boron (B); and forming a coating layer including boron (B).

[0060] Another aspect provides a method for preparing the positive electrode material of the above aspect, and the method comprises:

[0061] Preparing a first positive electrode active material, comprising: forming the first positive electrode active material in the form of single particles by mixing a transition metal precursor and a lithium raw material and then firing the resulting mixture; washing the positive electrode active material with water; and forming a coating layer containing boron (B) and cobalt (Co) on at least a portion of the surface of the positive electrode active material;

[0062] Preparing a second positive electrode active material, comprising: forming a second positive electrode active material in the form of a single particle having a particle size larger than that of a single particle of the first positive electrode active material by mixing a transition metal precursor and a lithium raw material and then firing the resulting mixture; washing the positive electrode active material with water; and forming a coating layer containing boron (B) and cobalt (Co) on at least a portion of a surface of the positive electrode active material; and

[0063] The first positive electrode active material and the second positive electrode active material are mixed.

[0064] According to one aspect, the preparing of at least one of the first positive active material and the second positive active material may further include: forming a coating layer including cobalt (Co) before forming the coating layer including boron (B); and forming the coating layer including boron (B).

[0065] The particle sizes of the first positive electrode active material and the second positive electrode active material can be controlled by changing process conditions such as firing temperature, firing time, and precursor synthesis time.

[0066] An exemplary preparation method of the above-mentioned first positive electrode active material and second positive electrode active material will be described.

[0067] The lithium nickel-based oxide can be prepared by mixing a transition metal precursor and a lithium raw material and then firing the resulting mixture. The precursor can be used by purchasing a commercially available precursor, or can be prepared by placing a transition metal aqueous solution, an ammonium cation complex forming agent and an alkaline compound in a reactor to perform a coprecipitation reaction under stirring.

[0068] For example, when an aqueous transition metal solution, an ammonium cation complex former, and a basic compound are placed in a reactor and stirred, precursor particles in the form of a transition metal hydroxide are generated while the transition metal in the aqueous transition metal solution is co-precipitated.

[0069] In this case, the transition metal aqueous solution, the ammonium cation complex forming agent, and the basic compound are added in such amounts that the pH of the reaction solution is within a desired range.

[0070] When the precursor particles are formed by the above method, the precursor is obtained by separating the precursor particles from the reaction solution.

[0071] The transition metal aqueous solution can be prepared by dissolving a transition metal-containing raw material in a solvent such as water, and can be prepared by dissolving, for example, a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, and / or an aluminum-containing raw material in water.

[0072] Meanwhile, the transition metal-containing raw material may be acetate, carbonate, nitrate, sulfate, halide, sulfide or oxide of the transition metal.

[0073] The nickel-containing raw material can be Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salt or nickel halide, etc., and any one of them or a mixture of two or more thereof can be used.

[0074] The cobalt-containing raw material may be Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O or Co(SO4)2·7H2O, and any one of them or a mixture of two or more thereof may be used.

[0075] The manganese-containing raw material can be manganese oxides, such as Mn2O3, MnO2 and Mn3O4; manganese salts, such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, dicarboxylic acid manganese salts, manganese citrate and fatty acid manganese salts; hydroxy oxide or manganese chloride, etc., and any one of them or a mixture of two or more thereof can be used.

[0076] If necessary, in addition to nickel, cobalt and manganese, the transition metal aqueous solution may further include a doping element (M). In this case, M may include at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo. When the positive electrode active material further includes a doping element, the effect of improving service life characteristics, discharge characteristics and / or stability can be achieved.

[0077] When the transition metal aqueous solution further contains a doping element M, a raw material containing the doping element M may be further selectively added during the preparation of the transition metal precursor.

[0078] As the raw material containing the doping element M, at least one or more selected from the group consisting of acetates, sulfates, sulfides, hydroxides, oxides, and oxyhydroxides containing the doping element M can be used.

[0079] Meanwhile, the ammonium cation complex forming agent can be at least one selected from the group consisting of NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4 and NH4CO3, and can be placed in the reactor in the form of a solution in which the compound is dissolved in a solvent. As the solvent, water or a mixture of water and an organic solvent (specifically alcohol, etc.) that can be uniformly mixed with water can be used.

[0080] Next, the alkaline compound can be selected from at least one of the group consisting of NaOH, KOH and Ca(OH)2, and can be placed in the reactor in the form of a solution in which the compound is dissolved in a solvent. In this case, as the solvent, a mixture of water or water and an organic solvent (specifically alcohol, etc.) that can be uniformly mixed with water can be used.

[0081] As lithium raw materials, lithium-containing sulfates, nitrates, acetates, carbonates, oxalates, citrates, halides, hydroxides and oxyhydroxides can be used, and for example, Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, Li3C6H5O7 or mixtures thereof can be used.

[0082] The precursor and the lithium raw material may be mixed so that the molar ratio of transition metal (Me) contained in the precursor: lithium (Li) is 1: 1 to 1: 1.2, preferably 1: 1 to 1: 1.1. When the lithium raw material is mixed in a range less than the above range, there is a risk of reduced capacity of the positive electrode active material to be prepared, and when the lithium raw material is mixed in a range exceeding the above range, the particles may sinter during firing, making it difficult to prepare the positive electrode active material, and capacity reduction and separation of the positive electrode active material particles after firing may occur.

[0083] If necessary, an M-containing material may be additionally mixed during firing. The doping element M may be at least one selected from the group consisting of, for example, W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and the raw material containing the doping element M may be at least one selected from the group consisting of acetates, sulfates, sulfides, hydroxides, oxides, or oxyhydroxides containing the doping element M.

[0084] The firing may be performed at 700° C. to 1,000° C. for 10 hours to 35 hours, and preferably at 750° C. to 900° C. for 15 hours to 30 hours, but is not limited thereto.

[0085] Subsequently, the fired uncoated positive active material is washed with water. Preferably, water washing is performed to remove the residual lithium by-product content in the positive active material of about 30% by weight or more, 40% by weight or more, or 50% by weight or more. For example, when the residual lithium by-product content in the uncoated positive active material before water washing is 1% by weight, the residual lithium by-product content in the washed positive active material can be 0.5% by weight. Here, residual lithium by-product refers to a compound containing lithium, such as LiOH, Li2CO3. Washing can be carried out under conditions that can achieve the above-mentioned residual lithium by-product content. Water washing can be carried out by mixing the fired positive active material with water and stirring the resulting mixture. In this case, the weight ratio of the positive active material to water can be 7:3 to 3:7, such as 5:5, and the water washing time can be determined as needed, for example, it can be more than 3 minutes or 5 minutes. Washing conditions including time, temperature and the weight ratio of active material to water can be carefully selected to achieve a suitable reduction in the content of residual lithium by-products.

[0086] Next, the lithium nickel-based oxide and the boron-containing coating raw material are mixed and then heat-treated to form a coating layer.

[0087] The boron-containing coating raw material may be, for example, H2BO3, HBO2, H3BO3, H2B4O7, B2O3, C6H5B(OH)2, (C6H5O)3B, (CH3(CH2)3O)3B, C3H9B3O6, and (C3H7O3)B, etc. The coating raw material is mixed in an amount such that the content of boron (B) is 200 ppm to 3,000 ppm based on the total weight of each positive electrode active material.

[0088] Meanwhile, the mixing of the lithium nickel-based oxide and the coating raw material may be performed by solid phase mixing, and the heat treatment may be performed at a temperature of 200° C. to 500° C. or 250° C. to 400° C., but is not limited thereto.

[0089] If necessary, a coating containing cobalt may be formed before forming a coating containing boron. In addition to using the above-mentioned cobalt-containing coating raw material, the same method as the method for forming a coating containing boron may be used. The cobalt-containing raw material may be one or more selected from the group consisting of Co3O4, Co(OH)2, Co2O3, Co3(PO4)2, CoF3, Co(OCOCH3)2·4H2O, Co(NO3)·6H2O, Co(SO4)2·7H2O and CoC2O4. In this case, it is preferred that the mixing amount of the cobalt-containing coating raw material is such that the content of cobalt is 5,000 ppm to 50,000 ppm based on the weight of each positive electrode active material.

[0090] Meanwhile, the positive electrode material of the present invention can be prepared by the following method: separately preparing a first positive electrode active material and a second positive electrode active material, then mixing the positive electrode active materials to form a mixture, mixing the mixture with a cobalt-containing coating raw material or a boron-containing coating raw material, and then heat treating to form a coating on the surfaces of the first positive electrode active material and the second positive electrode active material.

[0091] According to one aspect, the positive electrode active material having a boron-containing coating and / or a cobalt-containing coating has a residual lithium by-product content of less than 1 wt %, preferably less than 0.8 wt %, less than 0.7 wt %, less than 0.6 wt %, less than 0.55 wt % or less than 0.5 wt % based on 100 wt % of the positive electrode active material by performing the above-mentioned water washing process. The residual lithium by-product can be measured by the following method. The lithium by-product remaining on the surface of the coated positive electrode active material is dissolved by pouring 10g of the positive electrode active material into distilled water, and then only filtering the solution and titrating while injecting 0.1M HCl at a rate of 0.3 to 0.5mL / min. In this case, the residual lithium by-product content is calculated with the amount of HCl injected to pH 5. The device for pH titration is a device manufactured by Metrohm AG. The above-mentioned measurement can measure the positive electrode active material after forming the above-mentioned coating.

[0092] Another aspect of the present invention provides a positive electrode for a secondary battery, comprising: a current collector; and a positive electrode active material layer disposed on the current collector and comprising the positive electrode material of the above aspect.

[0093] The positive electrode active material layer may additionally include a binder and a conductive material.

[0094] According to one aspect, the positive electrode binder can be used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material particles and the positive electrode current collector. As the positive electrode binder, those known in the art can be used, and non-limiting examples thereof include: polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used.

[0095] The content of the positive electrode binder may be 0.1 parts by weight or more and 50 parts by weight or less, for example, preferably 0.3 parts by weight or more and 35 parts by weight or less, and more preferably 0.5 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the positive electrode active material layer.

[0096] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without particular limitation as long as the conductive material has electronic conductivity without causing chemical changes in the battery. Specific examples thereof include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used.

[0097] Specifically, in one aspect, the conductive material may include one or more of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). Based on 100 parts by weight of the composition for the positive electrode active material layer, the content of the conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.

[0098] According to another aspect of the present invention, a secondary battery positive electrode is provided, comprising: a current collector; and a positive electrode active material layer disposed on the current collector and comprising the positive electrode composition. The thickness of the positive electrode active material layer may be 20 μm or more and 500 μm or less.

[0099] The content of the positive electrode active material in 100 parts by weight of the positive electrode active material layer can be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 96 parts by weight or more and 99.9 parts by weight or less.

[0100] There is no particular limitation on the positive electrode current collector, as long as the current collector has conductivity without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc., can be used. In addition, the thickness of the positive electrode current collector can generally be 1 μm to 500 μm, and the adhesion of the positive electrode active material can also be enhanced by forming fine irregularities on the surface of the current collector. For example, the positive electrode current collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0101] Another aspect of the present specification provides a secondary battery comprising the positive electrode, the negative electrode, and the separator of the above aspect.

[0102] The negative electrode may include a current collector and a negative electrode active material layer disposed on the current collector.

[0103] According to one aspect, the negative electrode includes a silicon-based active material.

[0104] The active material containing SiO x (0≤x<2) as the silicon-based active material can be silicon-based composite particles containing SiO x (0<x<2) and pores.

[0105] SiO x (0<x<2) corresponds to the matrix in the silicon-based composite particles. SiO x (0<x<2) can be in the form including Si and SiO2, and Si can also form a phase. That is, x corresponds to the ratio of the number of O to Si contained in SiO x (0<x<2). When the silicon-based composite particles include SiO x (0<x<2), the discharge capacity of the secondary battery can be improved.

[0106] The silicon-based composite particles may further include at least one of a Mg compound and a Li compound. The Mg compound and the Li compound can correspond to the matrix in the silicon-based composite particles.

[0107] The Mg compound and / or the Li compound may be present inside and / or on the surface of SiO x (0<x<2). Through the Mg compound and / or the Li compound, the initial efficiency of the battery can be improved.

[0108] The Mg compound may include at least any one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The Mg silicate may include at least any one of Mg2SiO4 and MgSiO3. The Mg silicide may include Mg2Si. The Mg oxide may include MgO.

[0109] In one aspect of the present specification, based on a total of 100% by weight of the silicon-based active material, the content of the Mg element may be 0.1% by weight to 20% by weight, or 0.1% by weight to 10% by weight. Specifically, the content of the Mg element may be 0.5% by weight to 8% by weight or 0.8% by weight to 4% by weight. When the above range is satisfied, the Mg compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the silicon-based active material during the charge and discharge process of the battery can be easily inhibited, and the discharge capacity and the initial efficiency of the battery can be improved.

[0110] The Li compound may include at least any one selected from the group consisting of Li silicate, Li silicide, and Li oxide. The Li silicate may include at least any one of Li2SiO3, Li4SiO4, and Li2Si2O5. The Li silicide may include Li7Si2. The Li oxide may include Li2O.

[0111] In one aspect of the present invention, the Li compound may exist in the form of lithium silicate. Lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the silicon-containing composite particles in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5, and the amorphous lithium silicate may be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to this form.

[0112] In one aspect of this specification, based on a total of 100% by weight of the silicon-based active material, the content of the Li element may be 0.1% to 20% by weight, or 0.1% to 10% by weight. Specifically, the content of the Li element may be 0.5% to 8% by weight, and more specifically 0.5% to 4% by weight. When the above range is satisfied, the Li compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the negative electrode active material during the charge and discharge process of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0113] The content of the Mg element or the Li element can be confirmed by ICP analysis. For ICP analysis, a predetermined amount (about 0.01 g) of the negative electrode active material is accurately aliquoted, and then the negative electrode active material is completely decomposed on a hot plate by transferring the aliquot to a platinum crucible and adding nitric acid, hydrofluoric acid, or sulfuric acid thereto. Thereafter, a reference calibration curve is prepared by measuring the intensity of a standard liquid prepared using a standard solution (5 mg / kg) at the inherent wavelength of the Mg element or the Li element using an inductively coupled plasma atomic emission spectrometer (ICP AES, Perkin-Elmer 7300). Thereafter, the pretreated sample solution and the blank sample are each introduced into the device, the actual intensity is calculated by measuring each intensity, the concentration of each component relative to the prepared calibration curve is calculated, and then the content of the Mg element or the Li element of the prepared silicon-based active material can be analyzed by converting the sum to a theoretical value.

[0114] In one aspect of the present specification, the carbon layer may be disposed on the surface and / or inside the pores of the silicon-based composite particles. The carbon layer imparts electrical conductivity to the silicon-based composite particles, and the initial efficiency, service life characteristics, and battery capacity characteristics of a secondary battery including a negative electrode active material containing the silicon-based composite particles may be improved. Based on a total of 100% by weight of the silicon-based composite particles, the total weight of the carbon layer may be included in an amount of 5% to 40% by weight.

[0115] In one aspect of the present specification, the carbon layer may include at least any one of amorphous carbon and crystalline carbon.

[0116] The average particle size of silicon active materials (D 50 ) may be 2 μm to 15 μm, specifically 3 μm to 12 μm, and more specifically 4 μm to 10 μm. When the above range is met, the side reaction between the silicon-based composite particles and the electrolyte can be controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved.

[0117] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured using, for example, laser diffraction. Laser diffraction can generally measure particle sizes from the submicron region to several millimeters or so, and can obtain results with high reproducibility and high resolution.

[0118] According to one aspect of the present specification, the negative electrode active material layer may further include an additional negative electrode active material in addition to the above-mentioned silicon-based active material.

[0119] As an additional negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples thereof include: metal materials that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy; metal oxides that can be doped and dedoped with lithium, such as SiOβ (0<β<2), SnO2, vanadium oxide, lithium titanium oxide and lithium vanadium oxide; a composite comprising the above metal materials and a carbonaceous material, such as a Si-C composite or a Sn-C composite; or a carbon-based active material, etc., and any one of them or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material.

[0120] In one aspect of the present invention, a weight ratio of the silicon-based active material to the additional negative electrode active material contained in the negative electrode active material layer may be 1:99 to 90:10, specifically 1:99 to 50:50.

[0121] In one aspect of the present specification, carbon-based active materials can be used without any particular limitation, and as a representative example thereof, crystalline carbon, amorphous carbon or a combination thereof can be used. Examples of crystalline carbon include graphite, such as amorphous, plate-like, flaky, spherical or fibrous natural graphite and artificial graphite, and examples of amorphous carbon include soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide and fired coke, etc. Graphite can be natural graphite, artificial graphite or a mixture thereof. Based on 100 parts by weight of all negative electrode active materials contained in the negative electrode active material layer, the content of the carbon-based active material can be more than 60 parts by weight and less than 99 parts by weight.

[0122] In one aspect of the present specification, the content of the negative electrode active material in 100 parts by weight of the negative electrode active material layer can be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 96 parts by weight or more and 99.9 parts by weight or less.

[0123] According to another aspect of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the silicon-based active material and the carbon-based active material.

[0124] The negative electrode binder can be used to improve the bonding between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the negative electrode current collector. As the negative electrode binder, those known in the art can be used, and its non-limiting examples can include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and its hydrogen is replaced by Li, Na or Ca etc. At least one of the group consisting of materials, and various copolymers thereof can also be included.

[0125] The content of the negative electrode binder may be 0.1 parts by weight or more and 20 parts by weight or less, for example, preferably 0.3 parts by weight or more and 20 parts by weight or less, and more preferably 0.5 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer.

[0126] The negative electrode active material layer may not contain a conductive material, but if necessary, it may further contain a conductive material. The conductive material contained in the negative electrode active material layer is not particularly limited as long as the conductive material has conductivity without causing chemical changes in the battery, and for example, graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbon powders; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and conductive materials such as polyphenylene derivatives, etc. Based on 100 parts by weight of the negative electrode active material layer, the content of the conductive material in the negative electrode active material layer may be 0.01 parts by weight to 20 parts by weight, preferably 0.03 parts by weight to 18 parts by weight.

[0127] In one aspect of the present specification, the thickness of the negative electrode active material layer may be 10 μm or more and 500 μm or less.

[0128] In one aspect, as long as the negative electrode current collector has conductivity without causing chemical changes in the battery, the negative electrode current collector is sufficient and is not particularly limited. For example, as a current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel treated with carbon, nickel, titanium, silver, etc. on its surface can be used. Specifically, as a current collector, a transition metal (such as copper or nickel) that adsorbs carbon well can be used. Although the thickness of the current collector can be 1 μm to 500 μm, the thickness of the current collector is not limited thereto.

[0129] The positive electrode and the negative electrode can be manufactured by a typical manufacturing method of the positive electrode and the negative electrode, except that the aforementioned positive and negative electrode active materials are used. Specifically, after the composition for forming an active material layer containing the aforementioned active material and an optional binder and a conductive material is applied to the current collector, the positive electrode and the negative electrode can be manufactured by drying and rolling the current collector. In this case, the types and contents of the positive electrode active material and the negative electrode active material, the binder and the conductive material are as described above. The solvent may be a commonly used solvent in the art, examples of which include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, etc., and any one of them or a mixture of two or more thereof can be used. Considering the coating thickness and preparation yield of the composition, as long as the amount of the solvent dissolves or disperses the active material, the conductive material and the binder and has a viscosity that can show excellent thickness uniformity in the subsequent coating process of the positive and negative electrodes, the amount of the solvent used is sufficient. Alternatively, by another method, the positive electrode and the negative electrode may be manufactured by casting the active material layer-forming composition on a separate support and then laminating a film obtained by peeling from the support on a current collector.

[0130] In a secondary battery of one aspect, the efficiency Ec of the positive electrode may be less than the efficiency Ea of the negative electrode. According to one example, the ratio (Ec / Ea) of the efficiency Ec of the positive electrode to the efficiency Ea of the negative electrode is 0.5 to 0.8. As described above, when a lithium nickel-based oxide having a coating layer containing a specific material formed thereon is used as a positive electrode active material and a silicon-based active material is used as a negative electrode active material, the efficiency of the positive electrode and the efficiency of the negative electrode can complement the irreversible capacity of the negative electrode by having the aforementioned relationship.

[0131] The separator separates the negative electrode from the positive electrode and provides a mobile channel for lithium ions, and can be used without particular limitation, as long as the separator is generally used as a separator in a secondary battery, and in particular, preferably has excellent ability to retain the moisture of the electrolyte and has a low resistance to the movement of ions in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, a typical porous non-woven fabric can also be used, such as a non-woven fabric made of glass fiber and polyethylene terephthalate fiber with a high melting point. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.

[0132] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used to prepare lithium secondary batteries, but are not limited thereto.

[0133] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0134] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.

[0135] In particular, among carbonate organic solvents, cyclic carbonates ethylene carbonate and propylene carbonate can be preferably used because cyclic carbonates have a high dielectric constant as a high-viscosity organic solvent and thus dissociate lithium salts well, and because cyclic carbonates can be mixed with low-viscosity and low-dielectric-constant linear carbonates (e.g., dimethyl carbonate and diethyl carbonate) in an appropriate proportion and used to prepare an electrolyte with high conductivity, such cyclic carbonates can be more preferably used.

[0136] As the metal salt, a lithium salt can be used, which is a material that is easily dissolved in a non-aqueous electrolyte, and as the anion of the lithium salt, for example, a metal salt selected from F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the groups consisting of.

[0137] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the reduction of the battery capacity and increase the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, one or more additives may be further included, for example, halogenated-alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0138] A secondary battery of one aspect of the present invention includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, and may be a lithium secondary battery.

[0139] Another aspect of the present invention provides a battery module including the above-mentioned secondary battery as a unit cell and a battery pack including the battery module. The battery module and the battery pack include secondary batteries having high capacity, high rate characteristics and cycle characteristics, and can therefore be used as a power source for medium and large-sized equipment selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0140] Since the secondary battery of various aspects of the present invention stably exhibits excellent discharge capacity, output characteristics and cycle performance, the lithium secondary battery can be used as a power source for portable devices such as mobile phones, notebook computers and digital cameras, and medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems. For example, the battery module or battery pack can be used as a power source for one or more of the following medium and large devices: power tools; electric vehicles including electric vehicles (EV), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEV); and power storage systems.

[0141] Example

[0142] Hereinafter, preferred embodiments will be given to facilitate understanding of the present invention, but the embodiments are provided only for illustrating the present invention, and it is obvious to those skilled in the art that various changes and modifications may be made within the scope and technical spirit of the present invention, and it is obvious that such changes and modifications also fall within the appended claims.

[0143] Example 1

[0144] Will have Ni 0.84 Co 0.08 Mn 0.08The precursor composed of (OH)2 and LiOH in a molar ratio of (Ni+Co+Mn):Li of 1:1.06 were placed in a Hensel mixer (700L) and mixed at a center speed of 400rpm for 20 minutes. The mixed powder was placed in an aluminum crucible with a size of 330mmx330mm and heat treated at 760℃ for 12 hours in an oxygen (O2) atmosphere to prepare a Li 1.0 Ni 0.84 Co 0.08 Mn 0.08 O2 composition of lithium composite transition metal oxide. Thereafter, the prepared lithium composite transition metal oxide was mixed with water in a ratio of 1: 1, and the resulting mixture was stirred for 5 minutes and dried in a vacuum oven at 130 ° C for 12 hours to prepare a lithium composite transition metal oxide in the form of a single particle. Subsequently, the lithium composite transition metal oxide in the form of a single particle was dry mixed with 20,000 ppm of Co(OH)2 relative to the total weight of the lithium composite transition metal oxide. The mixture was heat treated at 600 ° C in an air atmosphere for 6 hours to prepare a lithium composite transition metal oxide in the form of a single particle having a cobalt coating formed thereon. The lithium composite transition metal oxide was dry mixed with 1200 ppm of H3BO3 relative to the total weight of the lithium composite transition metal oxide having a cobalt coating formed thereon, and then heat treated at 400 ° C for 5 hours to prepare a first positive electrode active material having a boron coating formed thereon. The second positive electrode active material was prepared in the same manner as the first positive electrode active material, except that under the conditions for preparing the first positive electrode active material, the firing temperature was 800 ° C and the boron coating content was 600 ppm.

[0145] A first positive electrode active material and a second positive electrode active material (which are lithium composite transition metal oxides in the form of single particles with a cobalt coating and a boron coating provided on a portion of the particle surface), a conductive material (CNT) and a binder (PVDF) are placed in a methylpyrrolidone (NMP) solvent in a weight ratio of 97:1:2 to provide a positive electrode slurry (the content of the solid content of the positive electrode slurry is 70 parts by weight of the total positive electrode slurry).

[0146] Here, the first cathode active material and the second cathode active material had D50 of 3 μm and 7 μm, respectively, as single particles, and the amounts of cobalt and boron were as shown in the following Table 1. The first cathode active material and the second cathode active material were mixed at a weight ratio of 5:5.

[0147] The prepared cathode slurry was coated on an Al current collector, dried at 130° C., and then roll-pressed at room temperature to fabricate a cathode.

[0148] A negative electrode active material including a SiO2-based active material and graphite (the content of the SiO2-based active material is 5 parts by weight of the total negative electrode active material), a conductive material (carbon black), a binder (SBR) and a thickener (CMC) are placed in a distilled water solvent at a weight ratio of 96:1:2:1 to prepare a negative electrode slurry (the content of the solid content of the negative electrode slurry is 50 parts by weight of the total negative electrode slurry).

[0149] The negative electrode slurry prepared above was coated on a Cu current collector, dried at high temperature, and then roll-pressed at room temperature to manufacture a negative electrode.

[0150] The separator is inserted between the positive electrode and the negative electrode manufactured as described above and assembled, an electrolyte is injected, and then activated to manufacture a battery cell.

[0151] -Electrolyte composition: 1M LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (volume ratio 3 / 7), vinylene carbonate (VC) / propane sultone (PS) (based on 100 parts by weight of electrolyte, the contents are 3 parts by weight and 1.5 parts by weight, respectively)

[0152] -Activation: 0.1C, 3 hours. Degassing after high temperature / room temperature aging after charging

[0153] The electrode density, discharge end resistance, room temperature service life and high temperature service life of the positive electrode are shown in Table 2 below.

[0154] The meanings or measurement methods of electrode density, discharge end resistance, room temperature service life and high temperature service life are as follows.

[0155] *Electrode density: (electrode weight / (electrode thickness*electrode area))

[0156] -Electrode weight: The weight of the slurry excluding the weight of the aluminum foil

[0157] -Electrode thickness: The thickness of the slurry layer excluding the thickness of the aluminum foil

[0158] *Discharge end resistance: The third discharge capacity (initial capacity) was measured by subjecting the manufactured cell to three 0.33C constant current / constant voltage (CC / CV) charges (0.05C cutoff) to 4.2V and 0.33C constant current (CC) discharges (2.5V cutoff). Thereafter, after charging as described above, the SOC was set to 5% by discharging at 0.33C, and pulse discharge was performed at 2C for 10 seconds to measure the resistance (initial resistance).

[0159] *Room temperature service life: The manufactured cells were cycled by 0.5C constant current / constant voltage (CC / CV) charging (0.05C cutoff) to 4.2V and 0.5C constant current (CC) discharge (2.5V cutoff) at room temperature (25°C). After repeating the experiment 100 times, the capacity and resistance were measured in the same manner as in Experimental Example 1 to measure the capacity retention rate (capacity after 100 times / initial capacity × 100%).

[0160] * High temperature service life: The manufactured cells were cycled by 1C constant current / constant voltage (CC / CV) charging (0.05C cutoff) to 4.2V and 1C constant current (CC) discharge (2.5V cutoff) at high temperature (45°C). After repeating the experiment 400 times, the capacity and resistance were measured in the same manner as when measuring the end-of-discharge resistance to measure the capacity retention rate (capacity after 100 times / initial capacity × 100%).

[0161] Examples 2 to 10

[0162] The same procedure as in Example 1 was performed except that the cobalt and boron coating contents or the average particle diameter (D50) in the first positive electrode active material and the second positive electrode active material were changed as shown in Tables 1 to 3 below.

[0163] Comparative Example 1

[0164] The experiment was conducted in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material were used, but water washing was not performed before forming the coating layer, and the coating layer containing boron was not formed.

[0165] Comparative Example 2

[0166] An experiment was performed in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material were used, but the coating layer containing boron was not formed.

[0167] [Table 1]

[0168]

[0169] [Table 2]

[0170]

[0171] [Table 3]

[0172]

[0173] As shown in Tables 1 to 3, it can be confirmed that in the embodiments, the discharge end resistance is higher, and the service life at room temperature and the service life at high temperature are more excellent compared with Comparative Examples 1 and 2. In particular, for Example 1, the first positive electrode active material contains a higher boron content compared with Examples 2, 8 and 9, so the discharge end resistance is excellent, and the room temperature and high temperature service life characteristics are higher. For Examples 1, 2 and 8, the average particle size is larger than that of Examples 3, 5 and 6, so the discharge end resistance is relatively larger, resulting in better room temperature and high temperature service life characteristics. Compared with Examples 9 and 10, Examples 1, 2 and 8 show better room temperature and high temperature service life characteristics due to the appropriate B content. For Examples 1 to 10, compared with Examples 11 and 12, the room temperature and high temperature service life characteristics are excellent due to the appropriate Co content.

[0174] The content of residual lithium byproducts was measured by pH titration. Since the pH range of residual lithium byproducts and LBO (lithium borate oxide) titration is similar, the example includes the amount of LBO coated by B in the LiOH value. However, Comparative Examples 1 and 2 did not form a B coating, so there was no LBO phase, and therefore the content of residual lithium byproducts was measured to be relatively low.

Claims

1. A positive electrode material, comprising: A first positive electrode active material, which is in the form of single particles and has a coating containing boron (B) and cobalt (Co) provided on at least a part of its surface; and A second positive electrode active material, the average particle size D50 of which is larger than the average particle size D50 of the first positive electrode active material, is in the form of single particles, and has a coating containing boron (B) and cobalt (Co) provided on at least a part of its surface.

2. The positive electrode material according to claim 1, wherein The D50 of the first positive electrode active material is 1 μm or more and 7 μm or less, and the D50 of the second positive electrode active material is 3 μm or more and 12 μm or less.

3. The positive electrode material according to claim 1, wherein The average particle size D50 of the second positive electrode active material is 0.5 μm to 7 μm larger than the average particle size D50 of the first positive electrode active material.

4. The positive electrode material according to claim 1, wherein In each of the first positive electrode active material and the second positive electrode active material, the ratio of the amount of boron to the amount of cobalt in the coating is 0.001 to 0.

2.

5. The positive electrode material according to claim 1, wherein The ratio of the cobalt content to the boron content contained in all of the first positive electrode active material and the second positive electrode active material is 5 to 70.

6. The positive electrode material according to claim 1, wherein Each coating of the first positive electrode active material and the second positive electrode active material includes a coating containing boron (B) and a coating containing cobalt (Co), and the coating containing cobalt (Co) is provided on at least a part of the surface of the first positive electrode active material or the second positive electrode active material, or is provided between the coating containing boron (B) and at least a part of the surface of the single particles.

7. The positive electrode material according to claim 1, wherein Each of the first positive electrode active material and the second positive electrode active material contains cobalt in an amount of 5000 ppm to 50000 ppm.

8. The positive electrode material according to claim 1, wherein The content of boron in the first positive electrode active material is higher than the content of boron in the second positive electrode active material.

9. The positive electrode material according to claim 1, wherein The weight ratio A / B of the content A of boron in the first positive electrode active material to the content B of boron in the second positive electrode active material is 1 to 3.

10. The positive electrode material according to claim 1, wherein Each of the first positive electrode active material and the second positive electrode active material contains boron in an amount of 200 ppm to 3000 ppm.

11. The positive electrode material according to claim 1, wherein The first positive electrode active material and the second positive electrode active material are lithium nickel-based oxides in which the molar ratio of nickel among metal elements other than lithium is 50 mol% or more.

12. The positive electrode material according to claim 11, wherein The lithium nickel-based oxide has a composition represented by the following Chemical Formula 1: [Chemical Formula 1] Li 1+x (Ni a Co b Mr c M d )O2 In Chemical Formula 1, M is one or more selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and x, a, b, c, and d are 0≤x≤0.2, 0.50≤a<1, 0<b≤0.25, 0<c≤0.25, 0≤d≤0.1, respectively, and a + b + c + d = 1.

13. The positive electrode material according to claim 1, wherein The weight ratio of the first positive electrode active material to the second positive electrode active material is 9:1 to 1:

9.

14. The positive electrode material according to claim 1, wherein Based on 100% by weight of the positive electrode active material, the residual lithium by-product content of each of the first positive electrode active material and the second positive electrode active material is 1% by weight or less.

15. A positive electrode for a secondary battery, comprising: a current collector; and A positive electrode active material layer is provided on the current collector and comprises the positive electrode material according to any one of claims 1 to 14.

16. A secondary battery comprising: The positive electrode according to claim 15; negative electrode; and Diaphragm.

17. The secondary battery according to claim 16, wherein The negative electrode includes a silicon-based active material.

18. The secondary battery according to claim 17, wherein The negative electrode further comprises a carbon-based active material.

19. The secondary battery according to claim 16, wherein The efficiency Ec of the positive electrode is less than the efficiency Ea of the negative electrode.

20. A method for preparing a positive electrode active material, the method comprising: preparing a single particle positive electrode active material by mixing a transition metal precursor and a lithium raw material and then firing the resulting mixture; washing the positive electrode active material with water; as well as A coating layer including boron (B) and cobalt (Co) is formed on at least a portion of a surface of the positive electrode active material.

21. The method according to claim 20, wherein: The step of forming a coating layer containing boron (B) and cobalt (Co) on at least a portion of the surface of the positive electrode active material includes: forming a coating layer containing cobalt (Co) before forming a coating layer containing boron (B); and forming a coating layer containing boron (B).

22. A method for preparing the positive electrode material according to any one of claims 1 to 14, the method comprising: Preparing a first positive electrode active material, comprising: forming the first positive electrode active material in the form of single particles by mixing a transition metal precursor and a lithium raw material and then firing the resulting mixture; washing the positive electrode active material with water; and forming a coating layer containing boron (B) and cobalt (Co) on at least a portion of the surface of the positive electrode active material; Preparing a second positive electrode active material, comprising: forming a second positive electrode active material in the form of a single particle having a particle size larger than that of a single particle of the first positive electrode active material by mixing a transition metal precursor and a lithium raw material and then firing the resulting mixture; washing the positive electrode active material with water; and forming a coating layer containing boron (B) and cobalt (Co) on at least a portion of a surface of the positive electrode active material; and The first positive electrode active material and the second positive electrode active material are mixed.

23. The method according to claim 22, wherein: When preparing at least one of the first positive electrode active material and the second positive electrode active material, the step of forming a coating containing boron (B) and cobalt (Co) on at least a portion of the surface of the positive electrode active material includes: forming a coating containing cobalt (Co) before forming a coating containing boron (B); and forming a coating containing boron (B).

Citation Information

Patent Citations

  • Method and related device for random access procedure

    KR1020220125334A